Synergy of Competence and Leadership in Improving Employee Commitment, Motivation, and Performance for Organizational Development: Systematic Literature Review - Isbat, Isbat; Tukiran, Martinus; Yusnita, Nancy; Sunaryo, Widodo; Munawir, Abdillah; Haris Maraden, Abdul (Pelopor Publikasi Akademika, 2024)
This study aims to identify the synergy between competence and leadership in improving employee commitment, motivation, and performance for organizational development. The methodology used in this study is meta-analysis with a focus on quality data from international journals indexed by Scopus. The tools used include VOSviewer software for article review and WordStat for descriptive statistical analysis. The results of the study show that competence and leadership have an important role in improving employee commitment, motivation, and performance. This study reveals that improvements in both variables can overcome various obstacles in organizational development. Effective leadership and strong competencies are able to increase employee commitment, develop creative abilities, provide leadership training, and motivate employees through the right organizational strategy. This research has several important implications. First, organizations that want to improve employee performance must focus on strengthening leadership and developing competencies. Good management of intervening variables will help in designing more effective strategies, which in turn will improve the overall performance of the organization. Second, the results of the study show that organizations not only need to rely on leadership and competence alone, but also must consider the context and conditions of other variables that can affect the final result. A more comprehensive and holistic approach is needed to face the challenges and dynamic changes in organizational development. Based on the findings of this study, it is recommended that organizations implement training and development programs that focus on improving competence and leadership.